Development of a knowledge, attitude and practice questionnaire on urine leakage with an indwelling urethral catheter for nurses in China. Issue 5 (11th December 2022) - Chen, Hanxi; Li, Xinxin; Cui, Hong; Xiao, Xiling; Zhang, Qiuping; Gao, Xiaowen
Abstract: Aim: A knowledge, attitude and practice questionnaire on urine leakage (UL) with an indwelling urethral catheter (IUC) was developed for nurses in China and validated. Design: Observational study. Methods: A systematic literature review, the Delphi method and focus group evaluation were used to develop the questionnaire, which was administered to 304 registered nurses at two hospitals in Guangdong, China. The validity and reliability of the questionnaire were assessed. Results: The 27‐item questionnaire had four dimensions: knowledge I (aetiology), knowledge II (prevention and treatment), attitude and practice. The questionnaire showed excellent content validity and reliability. Four factors accounted for 70.526% of the variance. The data were well‐fitted to the four‐factor construct model. The questionnaire can be used to measure the knowledge of UL with an IUC among nurses in China, along with related attitudes and practices. This can improve nursing care of patients with IUCs. No patient or public contribution.